2023
DOI: 10.17358/ijbe.9.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Brand Trust Capacity in Mediating Social Media Marketing Activities and Purchase Intention: A Case of A Local Brand That Go-Global During Pandemic

Abstract: Indonesia has an active number of social media users, as many as 191 million people in January 2022 which rise significantly during the pandemic. This study aims to understand how social media marketing activities affect consumer purchase intention that is mediated by brand trust in a go-global, local clothing brand. This study uses a quantitative method on 200 respondents through an online questionnaire that is distributed to the Instagram followers of one of the go-global brands that showcase their product i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Brand trust refers to the confidence and reliance consumers have in a brand's ability to meet their expectations and deliver on its promises [ 63 ]. The impact of brand trust (hereafter referred to as online brand trust or OBT) on online purchase intention is well-established in the literature, as it reduces perceived risk and fosters relationships with customers [ [64] , [65] , [66] ]. Consumer trust in Internet vendors is receiving increased attention, as highlighted by Chen and Dhillon [ 67 ] in their paper proposing three fundamental dimensions: competence, integrity, and benevolence.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Brand trust refers to the confidence and reliance consumers have in a brand's ability to meet their expectations and deliver on its promises [ 63 ]. The impact of brand trust (hereafter referred to as online brand trust or OBT) on online purchase intention is well-established in the literature, as it reduces perceived risk and fosters relationships with customers [ [64] , [65] , [66] ]. Consumer trust in Internet vendors is receiving increased attention, as highlighted by Chen and Dhillon [ 67 ] in their paper proposing three fundamental dimensions: competence, integrity, and benevolence.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The credibility of social media influencers has been established as a significant determinant of purchase intention, particularly in the beauty industry, underscoring the importance of credibility in influencer marketing [34]. Additionally, the mediating role of brand trust in the relationship between social media marketing activities and purchase intention has been highlighted, shedding light on the mechanisms through which social media influences consumer behaviour [35]. Furthermore, the impact of social media marketing activities on consumers' purchase intentions, particularly in the context of handloom clothes, has been investigated, with demographic variables such as age, gender, income, and cultural differences being considered as potential moderators in shaping purchase intentions [36].…”
Section: Social Media Influencermentioning
confidence: 99%
“…This suggests that the implementation of digitalization initiatives aimed at enhancing brand trust can exert a favourable influence on individuals' intentions to save. Several previous studies Ramadhani, J. Y., & Prasasti A [14] have demonstrated that the implementation of digital strategies positively impacts customer trust towards brands, consequently resulting in a heightened inclination to make purchases. This research was conducted to identify and analyze the factors that influence customers' intention to save in the context of Islamic banking services that have adopted digitalization, with a focus on the "brand trust" factor or trust in banking brands.…”
Section: Introductionmentioning
confidence: 99%